2022
DOI: 10.3389/fmats.2021.796476
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Approach to Design and Discover Sustainable Cementitious Binders: Strategies to Learn From Small Databases and Develop Closed-form Analytical Models

Abstract: To reduce the energy-intensity and carbon footprint of Portland cement (PC), the prevailing practice embraced by concrete technologists is to partially replace the PC in concrete with supplementary cementitious materials [SCMs: geological materials (e.g., limestone); industrial by-products (e.g., fly ash); and processed materials (e.g., calcined clay)]. Chemistry and content of the SCM profoundly affect PC hydration kinetics; which, in turn, dictates the evolutions of microstructure and properties of the [PC +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Moreover, unique features designed for UHTCs can be affixed to ML models to reduce the complexity of the database. Our studies 73,74 have demonstrated that the customized features can significantly improve the prediction accuracy of ML models for complex materials.…”
Section: Resultsmentioning
confidence: 86%
“…Moreover, unique features designed for UHTCs can be affixed to ML models to reduce the complexity of the database. Our studies 73,74 have demonstrated that the customized features can significantly improve the prediction accuracy of ML models for complex materials.…”
Section: Resultsmentioning
confidence: 86%
“…Meanwhile, the variable importance provides critical knowledge to develop analytical models. Our previous studies [53,65,67,74,[81][82][83] successfully harnessed this tool to craft user-friendly, closed-form analytical models for different materials.…”
Section: Resultsmentioning
confidence: 99%
“…This combination of bagging and two-step randomization effectively reduces both variance and bias errors, enhancing the model's reliability [49,50]. To avoid overfitting and underfitting, the hyperparameters of RF are optimized via the 10-fold cross-validation (CV) [51,52] and grid-search methods [51,53].…”
Section: Random Forest (Rf)mentioning
confidence: 99%
“…The rigorously trained model produces high-fidelity, a priori predictions of the C3S dissolution rate. It is notable that ML models can predict the hydration kinetics of PC at any given age, which has been shown in our previous studies [51][52][53]. This study only focuses on the dissolution kinetics at the initial period (i.e., undersaturated solution) because the hydration products precipitate and cause the solution to reach saturation after a short time of the dissolution of C3S.…”
Section: Introductionmentioning
confidence: 91%